The Napoleonic footprint: how administrative tradition influenced collaborative climate adaptation in Cartagena, Colombia (SciELO Preprints, 2026)
This article helps illustrate three of the six themes addressed in the introduction to this special issue: the specificities of the Latin American context, the role of national historical-institutional trajectories in shaping climate institutionality and policy, and the challenges of building capacities -in this case, collaborative capacities- for climate action. The study of a plan for climate adaptation in Cartagena, Colombia, sheds light on the influence of administrative traditions upon collaborative governance and its evolution throughout different stages of the policy process. The results expand on previous research about the flexibility of administrative traditions, suggesting that traditions -in this case, the Latin American variant of the Napoleonic tradition- allow for the introduction and success of practices alien to them under conditions of high perceived interdependence.  Maintaining the new, non-traditional approach, however, may depend on results reinforcing behavioral change -in this case, collaboration. A return to the default behavior under the administrative tradition can take place very quickly. Effective collaborative governance for local climate adaptation benefits from collaboration designs promoting positive intermediate outcomes (small wins) early in the collaborative process and civil society relentlessly reinforcing perceived interdependence in State actors.